In Vitro Bioeffects of Polyelectrolyte Multilayer Microcapsules Post-Loaded with Water-Soluble Cationic Photosensitizer - Alexey V. Ermakov; Roman A. Verkhovskii; Irina V. Babushkina; Daria B. Trushina; Olga A. Inozemtseva; Evgeny A. Lukyanets; Vladimir J. Ulyanov; Dmitry A. Gorin; Sergei Belyakov; Maria N. Antipina (Pharmaceutics, 2020)
Microencapsulation and targeted delivery of cytotoxic and antibacterial agents of photodynamic therapy (PDT) improve the treatment outcomes for infectious diseases and cancer. In many cases, the loss of activity, poor encapsulation efficiency, and inadequate drug dosing hamper the success of this strategy. Therefore, the development of novel and reliable microencapsulated drug formulations granting high efficacy is of paramount importance. Here we report the in vitro delivery of a water-soluble cationic PDT drug, zinc phthalocyanine choline derivative (Cholosens), by biodegradable microcapsules assembled from dextran sulfate (DS) and poly-l-arginine (PArg). A photosensitizer was loaded in pre-formed [DS/PArg]4 hollow microcapsules with or without exposure to heat. Loading efficacy and drug release were quantitatively studied depending on the capsule concentration to emphasize the interactions between the DS/PArg multilayer network and Cholosens. The loading data were used to determine the dosage for heated and intact capsules to measure their PDT activity in vitro. The capsules were tested using human cervical adenocarcinoma (HeLa) and normal human dermal fibroblast (NHDF) cell lines, and two bacterial strains, Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. Our results provide compelling evidence that encapsulated forms of Cholosens are efficient as PDT drugs for both eukaryotic cells and bacteria at specified capsule-to-cell ratios.